Mechanical Behaviour and Microstructure Characteristic of Concrete by Using Freshwater and Seawater - Mansyur Mansyur; Dian Permana (Salehan Institute of Higher Education, 2020)
The development of infrastructure in archipelago countries often faces difficulties and challenges due to the lack of fresh water. Hence, in some cases, the usage of seawater is favourable, in particular for concrete making. Little studies have been conducted on comparing the seawater, and freshwater concretes, especially on microstructure analysis. The objective of this study was to reveal the compressive strength, elasticity, and microstructure of concrete using seawater and freshwater as the mixing water. The methodology of this study was mix design, making test specimens, curing test specimens, and microstructure analysis. The tests of concretes were conducted for each sample with variations of 1, 3, 7, and 28 days and the mechanical behavior were tested using compressive strength and elasticity as parameters. At the same time, the microstructure was examined using an X-Ray Diffraction (XRD). The results showed an increase in compressive strength and elasticity of seawater and freshwater concretes at all variations with insignificant differences observed between the two types of concretes. It was also discovered that the formation of Friedel's salt (3CaO.Al2O3.CaCl2.10H2O) in the seawater concrete was not in the freshwater concrete. In conclusion, the differentiation of microstructure did not significantly affect the compressive strength and elasticity between seawater and freshwater in mixing concrete.